Eksistensi dan Kontribusi Pondok Pesantren Sabilul Muhtadin sebagai Pesantren Tertua dI Kabupaten Kotawaringin Timur - Hamdi, Saibatul; Muhajir, Ahmad (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2021)
Islamic boarding school is the oldest Islamic educational institution that has contributed a lot to the world of education. Sabilal Muhtadin Islamic Boarding School as one of the oldest Islamic boarding schools in East Kotawaringin contributes significantly to the world of Islamic education. This study aims to find out more about; (1) the history of the Sabilal Muhtadin Islamic Boarding School; (2) Tips for the foundation in maintaining the existence of Islamic boarding schools; and (3) the contribution of Islamic boarding schools to the world of Islamic education, especially in Kotawaringin Timur Regency. The method used is a qualitative method by collecting data through interviews, observation and documentation. The results showed that; (1) Sabilal Muhtadin Islamic Boarding School is the oldest Islamic boarding school in Kotawaringin Timur with more than half a century of age and has experienced rapid development over time. (2) Tips for the foundation in maintaining the existence of Islamic boarding schools include increasing levels of education, registering each level at the Ministry of Religion to make it legal and trustworthy, and providing technology to keep up with the times. (3) Islamic boarding school contribution to the world of Islamic education, especially in East Kotawaringin, is to produce quality alumni who play an important role in society. In addition, Sabilal Muhtadin has also been named the most dedicated cottage in Kotawaringin Timur.